Manipulation of the Periorbital Musculature - Langsdon, Phillip; Karter, Nicholas (Facial Plastic Surgery, 2018)
The resting and expressive states of the periorbital region contribute to perceived age, emotion, gender, race, and countenance. A thorough understanding of the periorbital musculature is essential for comprehensive facial rejuvenation. Surgical and nonsurgical manipulation of these muscles can lead to alterations in brow elevation, resting brow position, and dynamic periorbital rhytids. Both surgical and nonsurgical techniques can produce desired effects, and they are often used concomitantly to obtain optimal results.
Keywords: periorbital; glabella; brow; corrugator; procerus